Distance to the Pediatric Emergency Department and Nonurgent Visits in Friuli Venezia Giulia, Italy. Issue 3 (March 2018) - Valent, Francesca; Busolin, Anna
Abstract : Objectives: Our objective was to assess how the distance from home to the closest pediatric emergency department (ED) affects nonurgent emergency room visits among the child population of the Northeastern Italian region of Friuli Venezia Giulia. Methods: The study was based on the administrative databases of the Regional Health Information System of Friuli Venezia Giulia. For the year 2014, we abstracted the records of all white-triage–tag visits of children younger than 16 years from the databases of the 3 regional pediatric EDs located in the 3 main cities. Those records were individually linked to the regional population's georeferenced address database through an anonymous univocal identifier. For each child younger than 16 years living within 20 km from an ED, we calculated the linear distance between the ED and home address. Distances were grouped into 7 circular distance bands: less than 2, 2 to 4, 4 to 6, 6 to 8, 8 to 10, 10 to 15, and 15 to 20 km. Within each band, we calculated the rate of ED visits during the year. Results: In 2014, there were 12, 055 white-triage–tag visits accounting for 24.7% of all visits in the regional pediatric EDs. Although the overall rate of ED visits was different among the EDs, it decreased significantly with increasing distance to the ED, with a 6-fold difference between the innermost and the outermost bands. Conclusions: In Friuli Venezia Giulia, short distance is a prompter for inappropriate pediatric ED attendance. Further research is needed in this region to understand the parental standpoint to implement strategies promoting uniform behaviors within the regional boundaries.